The role of school leadership in relation to conflict management at school:: A survey based upon five empirical researches - Manolis, Kyriakos (Dia-noesis: A Journal of Philosophy, 2024)
The role of the manager is decisive in terms of the effective or non-effective management of conflicts, as through the techniques he chooses to use and many times through the leadership style he chooses to apply, he will influence the attitudes and perceptions of teachers towards disagreements and consequent conflicts.